Integrating High-Value Cost-Conscious Care into an Existing Medical School Curriculum - Sruthi Eapen; Aylmer Tan; Paul Gorman; Gretchen Scholl; Andrea Smeraglio (MedEdPORTAL)
Introduction High-value cost-conscious care (HVCCC) education has been shown to reduce wasteful health care spending. Incorporating HVCCC into a medical school curriculum can be challenging due to limited curricular time. We explored the feasibility of medical students creating HVCCC peer education within existing platforms at a single urban academic medical school. We reasoned that curricular changes could improve student knowledge, attitudes, and competency with HVCCC within 2 hours and 25 minutes of curricular time. Methods First-year medical student attitudes and understanding regarding HVCCC were evaluated via a survey before and after the delivery of a mixed asynchronous and in-person HVCCC curriculum created by two medical student peers. The curricula comprised three spaced asynchronous online sessions targeting HVCCC skill development followed by a gamified 90-minute clinical skills lab where students competed to determine the correct diagnosis at the lowest cost. Results One hundred and twenty-three medical students (out of 145 first-year medical students) completed the presurvey and indicated willingness to participate in the educational innovation, and 54 completed both surveys. Forty-two percent of students agreed/strongly agreed that the curriculum was effective/strongly effective at promoting cost-effective care. Sixty-five percent of students agreed they would likely use these resources during their clinical rotations. Comfort accessing HVCCC resources improved from 4% precurriculum to 41% postcurriculum. There was no significant difference in HVCCC knowledge pre- and postsurvey. Discussion This educational innovation demonstrated the feasibility of a peer-developed HVCCC curriculum in preclinical education that minimally impacted curricular time and improved student comfort in accessing cost-effective resources.